Manhaj Ṣināʿat Qāmūs al-Munawwir ʿArabī–Indūnīsī li-Aḥmad Warson Munawwir (Dirāsah Waṣfiyyah Taḥlīliyyah) - Jugrofiyah Najah (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2015)
In its linguistic sense, a dictionary is a reference book that contains a large collection of a language's vocabulary accompanied by explanations and definitions of their meanings. Dictionary entries are arranged according to a specific system, either alphabetically or thematically. One of the primary reasons for compiling dictionaries is the need to overcome linguistic limitations experienced by language users, particularly when learning a foreign language. Such limitations often stem from an inadequate command of vocabulary, which hinders effective communication and writing. One of the dictionaries widely used by students of Arabic is the Al-Munawwir Arabic–Indonesian Dictionary compiled by Aḥmad Warson Munawwir. This dictionary plays an important role in assisting learners in identifying the meanings of unfamiliar Arabic vocabulary. It adopts a distinctive methodology in the classification and organization of its lexical entries, which differs in several respects from the approaches employed in other dictionaries. The dictionary is extensively used in schools, Islamic boarding schools, and universities because it is suitable for learners at different educational levels, ranging from secondary education to higher education. For this reason, the author seeks to examine and analyze the methodology employed in the compilation of this dictionary.